Comparative metabolic study of planktonic and sessile cells in Salmonella Enteritidis ATCC 13076: Elucidating metabolic pathways driving biofilm formation - Yuliany Guillín; Claudia Ortiz; William Hidalgo (PLoS ONE, 2025)
Microorganisms tend to accumulate on surfaces, forming aggregates such as biofilms, which grant them resistance to various environmental stressors and antimicrobial agents. This ability has hindered the effective treatment of diseases caused by pathogenic microorganisms, including Salmonella, which is responsible for a significant number of deaths worldwide. This study aimed to compare the metabolic profiles of planktonic and sessile cells of Salmonella Enteritidis using a metabolomics approach. The metabolites extracted from the bacterial cells were analyzed by LC/MS approach. Raw data were analyzed using Thermo Xcalibur v 3.1 software. For data processing, XCMS was used for feature detection, retention time, correction and alignment. The data matrix was analyzed by uni- and multivariate statistical methods (PCA, PLS-DA, Heatmap) in MetaboAnalyst software v 6.0. A total of 121 metabolites were presumptively identified as differential metabolic characteristics between the two bacterial states, and they were associated with their corresponding metabolic pathways. Among the metabolites that exhibited positive modulation in planktonic cells were proline, phenylalanine, which act as precursors of essential metabolites and part of the stress adaptation mechanisms. In addition, putrescine and cadaverine, play crucial roles in growth, stress response, and cell stability In contrast, the most representative metabolites in sessile cells included lysine, adenosine, purines, pyrimidines, and citrate, mainly associated with maintaining cellular homeostasis, stress response and metabolic regulation. Finally, pathway enrichment analysis identified metabolic changes in 11 pathways, predominantly involving purine and pyrimidine metabolism, arginine and proline metabolism, and vitamin B6 metabolism. These findings facilitated the identification of potential metabolic pathways associated with biofilm formation in the sessile cells of Salmonella Enteritidis.